If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x+35=2x+43
We move all terms to the left:
4x+35-(2x+43)=0
We get rid of parentheses
4x-2x-43+35=0
We add all the numbers together, and all the variables
2x-8=0
We move all terms containing x to the left, all other terms to the right
2x=8
x=8/2
x=4
| 9/4a+7=16 | | (2x)^5=-55 | | y+100=0 | | .2x=10000 | | c/15=22 | | x+4/x-2=x+1/x | | -18x-18x-12=24 | | b/21=-3 | | (6n+2)(5n-8)=0 | | 68=d/4 | | 7(3w+2)/3=-7 | | -2x=-18-8x | | -0.5y=19.5 | | 15/x=105/28 | | 5/2x+11/3=x/2+5/3 | | -0.9=-0.4k | | 0.04m=5.2 | | 11x+44=3x-130 | | 83x −52=8 | | 4/5g=2/5 | | 6x-9=6x+10 | | 3(4s+5)=123 | | 5^(2x-1)=3^(3x) | | (2,3)x=0,4 | | 1/2+2-3/2x=1,5x-6 | | -0,8+0,2x=-0,2x | | v/6=1 | | 7t-6=2t+1 | | 32x−6⋅8x−24532x-6⋅8x-245=0 | | 6.7=a/7 | | 6x-3=2×+13 | | 6x-3=2× |